Effects of non-ablative Er:YAG laser on the skin and the vaginal wall: systematic review of the clinical and experimental literature - Hympanova, Lucie; Mackova, Katerina; El-Domyati, Moetaz; Vodegel, Eva; Roovers, Jan-Paul; Bosteels, Jan; Krofta, Ladislav; Deprest, Jan (International urogynecology journal, 2020)
INTRODUCTION AND HYPOTHESIS: Er:YAG laser is frequently used in dermatology and gynecology. Clinical studies document high satisfaction rates; however, hard data on the effects at the structural and molecular levels are limited. The aim of this systematic review was to summarize current knowledge about the objective effects of non-ablative Er:YAG laser on the skin and vaginal wall. METHODS: We searched MEDLINE, Embase, Cochrane, and the Web of Science. Studies investigating objectively measured effects of non-ablative Er:YAG laser on the skin or vaginal wall were included. Studies of any design were included. Owing to the lack of methodological uniformity, no meta-analysis could be performed and therefore results are presented as a narrative review. RESULTS: We identified in vitro or ex vivo studies on human cells or tissues, studies in rats, and clinical studies. Most studies were on the skin (n = 11); the rest were on the vagina (n = 4). The quality of studies is limited and the settings of the laser were very diverse. Although the methods used were not comparable, there were demonstrable effects in all studies. Immediately after application the increase in superficial temperature, partial preservation of epithelium and subepithelial extracellular matrix coagulation were documented. Later, an increase in epithelial thickness, inflammatory response, fibroblast proliferation, an increase in the amount of collagen, and vascularization were described. CONCLUSIONS: Er:YAG laser energy may induce changes in the deeper skin or vaginal wall, without causing unwanted epithelial ablation. Laser energy initiates a process of cell activation, production of extracellular matrix, and tissue remodeling.
Keywords: Animals; Female; Epidermis; Dermis; Laser; Resurfacing; ženské pohlaví; Vagina; vagina; Collagen; kůže; Histology; Skin; krysa rodu Rattus; lasery pevnolátkové; zvířata; Lasers, Solid-State; laserová terapie; Rats; Laser Therapy